Walking Football During Ramadan Fasting for Cardiometabolic and Psychological Health Benefits to the Physically Challenged and Aged Populations - Zainudin, Sueziani Binte; Salle, Dee Dee A.; Aziz, Abdul Rashid (Frontiers in Nutrition, 2022)
Concurrent exercise and intermittent fasting regimen for long periods has been shown to enhance cardiometabolic health in healthy individuals. As exercise and fasting confer health benefits independently, we propose that Muslims who are fasting, especially those experiencing health and clinical challenges, continually engage in physical activity during the Ramadan month. In this opinion piece, we recommend walking football (WF) as the exercise of choice among Muslims who are fasting. WF can be played by any individual regardless of the level of fitness, skills and age. WF has been shown to elicit cardiovascular and metabolic stress responses which are suitable for populations with low fitness levels. Most importantly, WF has the inherent characteristics of being a fun team activity requiring social interactions amongst participants, hence likely to encourage long-term consistent and sustainable participation.